Irrigation and Tillage Management Effects on Canopy Formation in Corn - R. M. Aiken; F. Lamm; A. A. AbouKheira (Kansas Agricultural Experiment Station Research Reports, 2017)
Effects of canopy formation and function are frequently represented in irrigation management models by crop coefficients, which can be used to calculate expected crop water requirements. Soil tillage alters the micro-environment of a developing corn canopy. The objective of this study was to evaluate irrigation capacity and tillage effects on seasonal changes in maize canopy and above-ground biomass productivity. Leaf area index (LAI) and above-ground biomass (AGB) were quantified by non-destructive methods during four growing seasons for corn under two irrigation capacities (1 in./4 days or 1 in./8 days) and three tillage regimes (no-tillage (NT), strip tillage (ST), or conventional tillage (CT)). Irrigation capacity and tillage effects were evaluated for each sampling period; seasonal trends were evaluated for year and treatment effects. Conventional tillage management resulted in earlier canopy formation and greater AGB accumulation during early vegetative growth in three of four years. No-tillage management resulted in extended canopy duration and greater AGB at tassel stage in two of four years; ST management resulted in greatest canopy duration in one year. Evaluated during four years, seasonal trends in LAI indicated earliest development under CT and delayed canopy development under NT management. The intermediate rate of canopy development of corn under ST management, and favorable yield and water productivity, indicates utility of ST management for irrigated corn production.
Keywords: Irrigation; tillage; corn; canopy